Kajian Mekanisme Perdagangan Hak Emisi Karbon Dan Kontroversi Perlakuan Akuntansi Atas Hak Emisi Karbon - Rikasari Rikasari; Hariyati Hariyati (AKRUAL: JURNAL AKUNTANSI, 2009)
AbstractThis article discusses the characteristics of carbon emissions as the negative externalities that previously could not be included in the financial statements. Further explains the history and development of carbon emission rights trading that allows negative externality can be recorded in financial accounting. Various methods are offered based on various accounting standards in order to record transactions of carbon emission rights trading compared and discussed. The complexity of the standard interpretation that is used to record a new problem in an effort to incorporate the negative externalities in the financial statements. At the end of this article, several recommendations for recording transactions of carbon emissions trading has to offer.